Penggunaan Metotreksat dalam Pengelolaan Plasenta In Situ pada Kehamilan Abdominal: Laporan Kasus - Zulmaeta zulmaeta; Dhini Novri (Fakultas Kedokteran Universitas Riau, 2023)
Woman, 33 years old, G6P5A0L5, diagnosed as acute abdomen due to rupture of 20-21 weeks abdominal pregnancy. The placenta is seen implanted in the lateral wall of the peritoneum, was decided to be left. On the 5th day, an ultrasound examination was performed. The size of the placenta was 6.59 x 9 x 6.86 cm. Follow-up was carried out at the Outpatient Clinic periodically for one year for the administration of methotrexate regimens, follow-up of beta-HCG levels, and follow-up of placental size. After one year, there was regression of placental up to 80% and beta-HCG was no longer detected.